2023
DOI: 10.1002/slct.202204288
|View full text |Cite
|
Sign up to set email alerts
|

N and P Co‐doped Green Waste Derived Hierarchical Porous Carbon as a Supercapacitor Electrode for Energy Storage: Electrolyte Effects

Abstract: N, P dual-doped watermelon peel-derived carbon (NPW) was prepared and found to exhibit a larger specific surface area of 1809 m 2 g À 1 and improved hierarchically interconnected pores than N-doped and P-doped carbons. The NPW electrode exhibits excellent electrochemical activity in a three-electrode setup with 1 M H 2 SO 4 , 6 M KOH, and 1 M Na 2 SO 4 electrolytes; with high specific capacitance (498.8, 397.6, and 378.6 F g À 1 at 1 A g À 1 , respectively) and an average capacitance retention of ∼ 96.9 % afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…This quick ion transport through the interconnected and uniform porous network of HP-NGC reduces its internal resistance, enabling high charge/discharge rates and hence improving the capacitance of the HP-NGC electrode. 19 However, the macropores present in the HP-NGC probably function as ion-buffering reservoirs, minimizing the diffusion distance of the electrolyte, and hence, promoting a consistent and efficient ion distribution throughout the electrode material. 18,28 The cycling performance of the developed electrodes is also carried out and shown in Figure 5g, which confirmed that the HP-NGC electrode retained 80% of its initial capacitance after 10,000 cycles with a remarkable Coulombic efficiency of 101%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This quick ion transport through the interconnected and uniform porous network of HP-NGC reduces its internal resistance, enabling high charge/discharge rates and hence improving the capacitance of the HP-NGC electrode. 19 However, the macropores present in the HP-NGC probably function as ion-buffering reservoirs, minimizing the diffusion distance of the electrolyte, and hence, promoting a consistent and efficient ion distribution throughout the electrode material. 18,28 The cycling performance of the developed electrodes is also carried out and shown in Figure 5g, which confirmed that the HP-NGC electrode retained 80% of its initial capacitance after 10,000 cycles with a remarkable Coulombic efficiency of 101%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, they seriously suffer from agglomeration during solution processing, which restricts their surface area and reaction kinetics to result in low volumetric capacitance (∼<60 F cm –3 ) and energy density . Recent studies , indicate that the preparation of heteroatom-doped biomass-derived carbon with adjusted pore structures could be a potential strategy to enhance the electrochemical storage performances of carbon-based SCs by improving surface wettability, , electrolyte diffusion, and pseudocapacitance (PC). ,, For instance, Liang et al have synthesized N- and sulfur (S)-codoped hierarchical porous carbon electrodes from foxtail grass seeds through a multistep method, including freeze-drying and pyrolysis at different temperatures with the addition of mixed additives like NaHCO 3 and KHCO 3 in 1:1 weight ratio to deliver a moderate volumetric capacitance of 243.4 F cm –3 at 0.5 A g –1 and an electrode energy density of 33.8 Wh L –1 in 6 M KOH having a limited potential window of 1 V. In another report, N- and oxygen (O)-codoped carbon electrodes were prepared from soybean dregs through time- and energy-consuming multistep heating, including the hydrothermal method at 100 °C for 6 h followed by conventional carbonization at 650 °C for 2 h using KOH as an activating agent. Moreover, the developed material showed an inferior volumetric capacitance of 247.6 F cm –3 and an energy density of 34.3 Wh L –1 at 0.5 A g –1 in 6 M KOH in a limited potential window of 1 V .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include lipid peroxidation, oxida-tive stress, proteolysis, ROS induction, and cell membrane lysis. [39,40]…”
Section: Plausible Mechanism For Dye Degradationmentioning
confidence: 99%